2018
DOI: 10.3389/fneur.2018.00577
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke Depression Biomarkers: A Narrative Review

Abstract: Poststroke depression (PSD) is the most prevalent psychiatric disorder after stroke, which is independently correlated with negative clinical outcome. The identification of specific biomarkers could help to increase the sensitivity of PSD diagnosis and elucidate its pathophysiological mechanisms. The aim of current study was to review and summarize literature exploring potential biomarkers for PSD diagnosis. The PubMed database was searched for papers published in English from October 1977 to December 2017, 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 108 publications
(117 reference statements)
0
37
0
2
Order By: Relevance
“…Inflammatory cytokines were also thought to be related to the development of poststroke depression [23,24]. Jioa and colleagues found that interleukin (IL)-6 was elevated in patients with post-stroke depression, even after controlling for confounders, with a confidence interval of 95% [23].…”
Section: Biomarkers Associated With Poststroke Depressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inflammatory cytokines were also thought to be related to the development of poststroke depression [23,24]. Jioa and colleagues found that interleukin (IL)-6 was elevated in patients with post-stroke depression, even after controlling for confounders, with a confidence interval of 95% [23].…”
Section: Biomarkers Associated With Poststroke Depressionmentioning
confidence: 99%
“…Jioa and colleagues found that interleukin (IL)-6 was elevated in patients with post-stroke depression, even after controlling for confounders, with a confidence interval of 95% [23]. The elevation of IL-6 in patients that have strokes could possibly predict the development of poststroke depression [23,24]. In another meta-analysis, brain-derived neurotrophic factor (BDNF) was found to be involved in the development of depression and poststroke depression [25,26].…”
Section: Biomarkers Associated With Poststroke Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Практически все антидепрессанты улучшают нейрогенез и зачастую повышают концентрацию нейротрофических факторов, что поддерживает гипотезу нейрогенеза.Salinas J. et al[32] показали, что наличие эмоциональной поддержки связано с повышенным уровнем BDNF в сыворотке и сниженным риском развития деменции и инсульта, в то время как только уровень BDNF вносит небольшой вклад в развитие этих заболеваний. Снижение концентрации BDNF в сыворотке крови после инсульта может использоваться как предиктор возникновения постинсультной депрессии[33]. Kim et al[34] продемонстрировали, что гиперметилирование промотора BDNF коррелирует с распространенностью и частотой постинсультной депрессии, а также с тяжестью депрессии в течение 1 года после инсульта.…”
unclassified